Dive into UDL : immersive practices to develop expert learners - Grant, Kendra; Pérez, Luis, 1972- (International Society for Technology in Education, 2018)
Universal Design for Learning (UDL) is a framework for designing instruction that meets the needs of every learner. This book provides an overview of UDL, showing how to offer flexibility in methods of presentation, student participation and expression to support high achievement for all students, including those with disabilities or limited English proficiency.